2004
DOI: 10.1128/jb.186.11.3570-3577.2004
|View full text |Cite
|
Sign up to set email alerts
|

Novel Genes That Influence Development inStreptomyces coelicolor

Abstract: Filamentous soil bacteria of the genus Streptomyces carry out complex developmental cycles that result in sporulation and production of numerous secondary metabolites with pharmaceutically important activities. To further characterize the molecular basis of these developmental events, we screened for mutants of Streptomyces coelicolor that exhibit aberrant morphological differentiation and/or secondary metabolite production. On the basis of this screening analysis and the subsequent complementation analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 45 publications
(49 reference statements)
2
22
0
Order By: Relevance
“…Besides the aforementioned growth reduction, AK39 was defective in sporulation on MM supplemented with L-methionine and L-threonine, but not on sporulation agar. This Wnding accorded well with that of Gehring et al [9] who reported that an L-methionine auxotroph of S. coelicolor had developmental defects which also increased secondary metabolite production. A functional metH (methionine synthase gene) was required for conversion of aerial hyphae into chains of spores in this mutant.…”
Section: Disruption Of the Hom Gene In S Clavuligerussupporting
confidence: 88%
“…Besides the aforementioned growth reduction, AK39 was defective in sporulation on MM supplemented with L-methionine and L-threonine, but not on sporulation agar. This Wnding accorded well with that of Gehring et al [9] who reported that an L-methionine auxotroph of S. coelicolor had developmental defects which also increased secondary metabolite production. A functional metH (methionine synthase gene) was required for conversion of aerial hyphae into chains of spores in this mutant.…”
Section: Disruption Of the Hom Gene In S Clavuligerussupporting
confidence: 88%
“…It was suggested that the three proteins are involved in transducing an environmental signal that influences developmental progression and that SCO4542 mutants are abnormally rich in a cell type that produces pigmented antibiotics (192). Streptomycetes all have multiple gene clusters comprising paralogues of SCO4542 to -4 (191,193). One such cluster is the abaA cluster, discovered earlier through its presence in a DNA fragment that stimulated S. coelicolor colony pigmentation at high copy number (194).…”
Section: How Does Bldd Regulate Development and Antibiotic Production?mentioning
confidence: 99%
“…Methionine synthase is a vitamin B 12 -dependent enzyme that catalyses the final step in methionine biosynthesis, the conversion of homocysteine to methionine. Recent study showed that the disruption of the metH gene in S. coelicolor not only affected vegetative growth on minimal medium, but on rich medium blocked the conversion of aerial hyphae into chains of spores (Gehring et al, 2004). Glutamine synthetase is responsible for the ATPdependent synthesis of glutamine from ammonium and glutamate.…”
Section: Orthologous Phx Genes In Two Streptomyces Genomesmentioning
confidence: 99%